Current Application of Functional/Targeted Echocardiogram in NICU: An Update (Cardiovascular Journal, 2017)
Functional echocardiograph is the bedside use of cardiac ultrasound to monitor functional and hemodynamic changes longitudinally. It can assist in an understanding of pathophysiology of the rapidly changing neonatal hemodynamic status including cardiac function and systemic and pulmonary blood flow in critically ill preterm and term neonates. It also facilitates the evaluation of response to therapeutic intervention. This review examines the potential applications of functional echocardiography in different disease states, and how the technology may be introduced safely in the NICU.Cardiovasc. j. 2017; 10(1): 74-83